Methylene Blue Preserves Cytochrome Oxidase Activity and Prevents Neurodegeneration and Memory Impairment in Rats With Chronic Cerebral Hypoperfusion - Auchter, Allison M.; Barrett, Douglas W.; Monfils, Marie H.; Gonzalez-Lima, F. (Frontiers in Cellular Neuroscience, 2020)
Chronic cerebral hypoperfusion in neurocognitive disorders diminishes cytochrome oxidase activity leading to neurodegenerative effects and impairment of learning and memory. Methylene blue at low doses stimulates cytochrome oxidase activity and may thus counteract the adverse effects of cerebral hypoperfusion. However, the effects of methylene blue on cytochrome oxidase activity during chronic cerebral hypoperfusion have not been described before. To test this hypothesis, rats underwent bilateral carotid artery occlusion or sham surgery, received daily 4 mg/kg methylene blue or saline injections, and learned a visual water task. Brain mapping of cytochrome oxidase activity was done by quantitative enzyme histochemistry. Permanent carotid occlusion for one month resulted in decreased cytochrome oxidase activity in visual cortex, prefrontal cortex, perirhinal cortex, hippocampus and amygdala, and weaker interregional correlation of cytochrome oxidase activity between these regions. Methylene blue preserved cytochrome oxidase activity in regions affected by carotid occlusion and strengthened their interregional correlations of cytochrome oxidase activity, which prevented neurodegenerative effects and facilitated task-specific learning and memory. Brain-behavior correlations revealed positive correlations between performance and brain regions in which cytochrome oxidase activity was preserved by methylene blue. These results are the first to demonstrate that methylene blue prevents neurodegeneration and memory impairment by preserving cytochrome oxidase activity and interregional correlation of cytochrome oxidase activity in brain regions susceptible to chronic hypoperfusion. This demonstration provides further support for the hypothesis that lower cerebral blood flow results in an Alzheimer’s-like syndrome and that stimulating cytochrome oxidase activity with low-dose methylene blue is neuroprotective.